Growth performance of Intsia palembanica under the canopy of Pterocymbium javanicum - Abdul Aziz, Nor Farah Wahidah (2016)
At present, most forest plantations preferred fast-growing commercial tree species as they are able to meet the needs of the domestic market as compared to slow-growing hardwood species such as Intsia palembanica. This slow growing heavy-hardwood species are depleting in the natural forest and demand of this tree species is very high in the timber market. The status of this species under IUCN Red List is vulnerable because the risk to facing extinction due to deforestation is still a major threat for this species. Therefore, a trial planting has conducted at Ragut 3, Ladang Universiti Putra Malaysia, Puchong Selangor with the objective of evaluating the growth performance of Intsia palembanica under the canopy of Pterocymbium javanicum. This study consisted of two blocks with the different canopy development of P. javanicum with the maximum crown diameter of 1.59 m (at Block 1) with percentage of light penetration about 80% and 3.4 m (at Block 2) with percentage of light penetration about 40%. Each tree was planted at spacing 1.5 x 2.5 m. Data on growth and physiological were recorded within four months for the study period. Based on the independent sample T-test result, the (p>0.05) growth parameters of I. palembanica for both Block 1 and Block 2 shows there is no significant difference. This result indicates that the trees can adapt for different light conditions.